A multi-level researcher development framework to address contrasting views of student research challenges - Albertyn, R.; van Coller-Peter, S.; Morrison, J. (South African Journal of Higher Education, 2018)
Ensuring quality and completion of students’ research places pressure on postgraduate supervisors. Postgraduate students’ primary interest in theoretical and practical knowledge rather than research, influences the completion of qualifications. Student research challenges were explored using an Interactive Qualitative Analysis research design. Through conducting student and supervisor focus groups and individual interviews, issues emerged related to educational input, support and identity development. There were differences in the perspectives of student and supervisor indicating that students are less dependent on supervisors than supervisors thought they were. Supervisors indicated support strategies, such as an awareness of learning styles, adaptive support and strengthening researcher identity. Researcher development needs to take place on multiple levels to enhance quality and relieve pressure on the postgraduate supervisor in changing educational contexts.